Journey to health. Lesson 2, Stress. Part 4 - Dyer, Julia; Dallas County Community College District (Dallas, TX : Dallas County Community College District, 2003)
This video from the Dallas County Community College District talks about practical solutions to managing stress. Part 4 of 6.
"Mind, body, spirit".
Title from resource description page (viewed May 31, 2019).
In English.
Keywords: Health; Health planning; Health behavior; Mental health; Stress management; Anxiety; Santé.; Santé publique -- Planification; Habitudes sanitaires; Santé mentale; Gestion du stress; health; mental health; Anxiety; Health; Health behavior; Health planning; Mental health; Stress management; Instructional films; Instructional films; Films de formation